Music Therapy in Mental Health and Emotional Diversion of Primary and Secondary School Students - Dong Li (Occupational Therapy International)
The purpose of this paper is to provide a group music therapy intervention for elementary and middle school students with mood disorders through music therapy. To explore the improvement of group music therapy on the dysphoria and state of adolescent patients with mood disorders and to explore the relationship with self-identity. A music activity-based mental health education curriculum was designed based on the results of the current survey, while two homogenous classes were selected as the experimental and control classes; subsequently, the experimental teaching of the music activity-based mental health education curriculum was conducted in the experimental class, and the regular school mental health education curriculum was conducted in the control class, and the pre- and postexperimental scale tests were used to analyze that the curriculum of this study had a positive effect of this study’s curriculum on elementary school students’ positive emotions analyzed through pre- and postexperimental scale tests. The music activity-based mental health education program had a significant positive effect on the overall level of positive emotions of elementary school students, especially in the positive emotion index, happiness index, mental toughness, goal focus, and interpersonal assistance factor. The positive psychology-oriented music activity-based mental health education curriculum is well suited for elementary and middle school students, especially for upper elementary and middle school students. The music activity-based mental health education curriculum realizes the value of applying positive psychology to mental health education efforts at the elementary school level and flexibly uses a variety of related theories to promote positive emotional experiences for elementary and middle school students.